Inhaled platelet vesicle-decoyed biomimetic nanoparticles attenuate inflammatory lung injury - Jin, Hua; Luo, Renxing; Li, Jianing; Zhao, Hongxia; Ouyang, Suidong; Yao, Yinlian; Chen, Dongyan; Ling, Zijie; Zhu, Weicong; Chen, Meijun; Liao, Xianping; Pi, Jiang; et al. (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is an inflammation response which causes serious damages to alveolar epithelia and vasculature. So far, ALI still remains high lethality and mortality and there is no effective pharmacological management in the clinic. In this work, based on the inflammatory homing of platelets and cell membrane cloaking nanotechnology, we developed a biomimetic anti-inflammation nanoparticle delivery system for ALI treatment. PM@Cur-RV NPs were designed by combining the poly(lactic-co-glycolic acid) nanoparticles coated with platelet membrane vesicles (PM) to obtain the purpose for high targeting delivery of curcumin (Cur) and resveratrol (RV) to inflammatory lungs. In vitro and in vivo, PM@Cur-RV NPs showed good biocompatibility and biosafety. As expected, accumulation of NPs into the lung tract was observed after inhaled NPs. Remarkably, inhalation of PM@Cur-RV NPs effectively inhibited lung vascular injury evinced by decreased lung vascular permeability, and reduced proinflammatory cytokine burden in an ALI mouse model. The analysis of infiltrated macrophages in lungs showed that Cur-RV-modulated macrophage polarized towards M2 phenotype and decrease in histone lactylation might contribute to their anti-inflammation effects. Together, this work highlights the potential of inhalation of biomimetic nanoparticle delivery of herbal medicine for the management of pulmonary diseases.